Is Sexual Conflict an “Engine of Speciation”? - Gavrilets, Sergey (Cold Spring Harb Perspect Biol, 2014)
At the end of the last century, sexual conflict was identified as a powerful engine of speciation, potentially even more important than ecological selection. Earlier work that followed—experimental, comparative, and mathematical—provided strong initial support for this assertion. However, as the field matures, both the power of sexual conflict and constraints on the evolution of reproductive isolation as driven by sexual conflict are becoming better understood. From theoretical studies, we now know that speciation is only one of several possible evolutionary outcomes of sexual conflict. In line with these predictions, both experimental evolution studies and comparative analyses of fertilization proteins and of species richness show that sexual conflict leads to, or is associated with, reproductive isolation and speciation in some cases but not in others. Increased genetic variation (especially in females) without reproductive isolation is an underappreciated consequence of sexually antagonistic selection.